Marketing Strategy for the Promotion of Access to Cervical Cancer Screening for The Women in Tambon Ban Phaoe, Changwat Samut Sakhon - Poonpanit, Yuttana (Journal of Health Science of Thailand, 2019)
The objective of this action research was to study the result of the implementation of the marketing strategy for the promotion of access to cervical cancer screening for the women in Tambon Ban Phaoe, Ban Phaoe District, Changwat Samut Sakhon during April - September 2006. Applied marketing promotion strategy was employed as a guideline for enhancing perception in accordance with Health Belief Model and creating motive factors to increase intention in access to cervical cancer screening in the targeted group. The Health Belief Model perception on cervical cancer, an intention in access to screening, and the change of screening access rates were investigated in this study. Data from both cervical cancer screening monthly reports of Ban Phaoe hospital (Public Organization) and interviews the two independent groups of 83 samples in the year before and after the implementation. Selection was made proportional to its targeted population of each Moo Ban within Tambon Ban Phaoe, by using simple random technique. Statistical tests including frequency distribution, percentage, mean, standard deviation and t-test were employed. The results showed that Health Belief Model perception on cervical cancer and intention in access to cervical cancer screening of sample in the operation among the target group was at a high level, while it was at a medium level. Also, statistically, it was found that perception and intention of these two groups were significantly different. Besides, the cervical cancer screening access rate of the year before operation of the target population was higher than that of the year before operative target population. The result confirmed that marketing strategy could be applied in increasing cervical cancer screening access rate in the target group. Hence, it is recommended that the model in this study may be replicated in areas other than Tambon Ban Phaoe, Changwat Samut Sakhon.